Peacebuilding and corruption - Philp, M (Routledge, 2008)
The article argues that questions of definition relating to corruption are central to understanding its significance and its prominence in peacekeeping contexts. Definitional issues are discussed and a definition that combines universal features while acknowledging the importance of local norms and rules is offered. The definition revolves around actions, decisions and processes that subvert or distort the nature of public office and the political process. The challenge for peacebuilders is to develop and enforce standards for public office that have sufficient linkage with local norms and expectations to commond some support, and to do so in a context that, by definition, lacks consensus on norms and principles of legitimacy for public office. The article explores some of the strategies open to those in post-conflict contexts and argues that corruption will frequently be a rational strategy for many, creating a vicious cycle that is hard to break. The article also questions how far corruption should be the major concern of peacekeeping forces, and how the concept might be disaggregated to allow a more targeted approach - one that recognizes that attacking corruption directly may not always be the best strategy, and that sees that corruption may not always be the major priority.